How Can We Reap Learning Benefits for Individuals With Growth and Fixed Mindsets?: Understanding Self-Reflection and Self-Compassion as the Psychological Pathways to Maximize Positive Learning Outcomes - Kwan, Letty Y. -Y.; Hung, Yu Sheng; Lam, Lam (Frontiers in Education, 2022)
Having a growth mindset has been hailed as one of the most critical advancements in understanding students' motivation in recent years. The attention on the growth mindset indicates an increased surge in the public's interest in using evidence-based intervention models to facilitate learning. Because the positive benefits of growth mindsets are apparent, changing ones' mindset becomes the core focus of growth mindset literature. But aside from "changing" student's mindsets, finding the right kind of psychological interventions that leverage on student's growth or fixed mindset with sustainable improvement for students can be as, if not more important. The current study seeks to fill this research gap. Our first study indicated that learners with a relatively high growth mindset benefit from a self-reflection learning strategy. However, this very same self-reflection strategy can harm the learning benefits for those learners with a fixed mindset. The second study used experimental manipulation to show that learners with a growth mindset can enhance their learning process and outcomes from self-reflection strategies. In contrast, learners with a fixed mindset can improve their learning process and result from self-compassion strategies. The current study identified two distinct psychological mechanisms – self-reflection and self-compassion, and link them with mindsets with the learning process and learning outcomes. It also demonstrates how learners with growth and fixed mindsets can benefit from these two psychological mechanisms directly in an experimental design.